Prednisolone in early pregnancy inhibits regulatory T cell generation and alters fetal and placental development in mice. (11th March 2020) - Kieffer, Tom EC; Chin, Peck Y; Green, Ella S; Moldenhauer, Lachlan M; Prins, Jelmer R; Robertson, Sarah A
Abstract: Corticosteroids have been utilised in the assisted reproduction setting with the expectation of suppressing aberrant immune activation and improving fertility in women. However, the effects of corticosteroids on fertility, and on pregnancy and offspring outcomes, are unclear. In this study, mice were administered prednisolone (1 mg/kg) or PBS daily in the pre-implantation phase, and effects on the adaptive immune response, the implantation rate, fetal development and postnatal outcomes were investigated. Prednisolone disrupted the expected expansion of CD4 + T cells in early pregnancy, inhibiting generation of both regulatory T cells (Treg cells) and effector T cells and suppressing IFNG required for T cell functional competence. Prednisolone caused an 8–20% increase in the embryo implantation rate and increased the number of viable pups per litter. In late gestation, fetal and placental weights were reduced in a litter size-dependent manner, and the canonical inverse relationship between litter size and fetal weight was lost. The duration of pregnancy was extended by ~ 0.5 day and birth weight was reduced by ~ 5% after prednisolone treatment. Viability of prednisolone-exposed offspring was comparable to controls, but body weight was altered in adulthood, particularly in male offspring. Thus, while prednisolone given in the pre-implantation phase in mice increases maternal receptivity to implantation and resource investment in fetal growth, there is a trade-off in long-term consequences for fetal development, birth weight and offspring health. These effects are associated with, and likely caused by, prednisolone suppression of the adaptive immune response at the outset of pregnancy.